CULTURAL RESILIENCE IN KAMPUNG MAHMUD AS AN EFFORT TO PRESERVE HISTORIC AREA - Puspitasari, Cynthia (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2019)
In order to achieve the concept of sustainable cities and communities, the historical and cultural richness of a city becomes one of the main sustainability modalities. The historical and cultural heritage of a city should be an important object protected by its existence and provide an identity. One of the important cultural heritages around Bandung is Kampung Mahmud. Kampung Mahmud is located 1.5 kilometres from the city of Bandung. This traditional village still holds the customs as cultural heritage and contribute to the development and spread of Islam in the city of Bandung. The existence of this village becomes an irony when its location lies between city life with all its modernity. How can the traditional kampung be able to have cultural resilience against other influences and challenges that can threaten sustainability? The study aimed to find the role of cultural resilience in Kampung Mahmud. The method used is a qualitative method that relates the instrument of cultural resilience theory to the facts that occur in the object of study. The output of this research is the principles of cultural resilience is successfully applied to Kampung Mahmud and can be an example for other regions.